2002
DOI: 10.1038/sj.eye.6700133
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of diabetic retinopathy: old concepts and new questions

Abstract: Hyperglycaemia appears to be a critical factor in the aetiology of diabetic retinopathy and initiates downstream events including: basement membrane thickening, pericyte drop out and retinal capillary non-perfusion. More recently, focus has been directed to the molecular basis of the disease process in diabetic retinopathy. Of particular importance in the development and progression of diabetic retinopathy is the role of growth factors (eg vascular endothelial growth factor, placenta growth factor and pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
199
0
12

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(215 citation statements)
references
References 252 publications
(236 reference statements)
4
199
0
12
Order By: Relevance
“…The vascular changes that occur in DR are well documented, and include loss of pericytes and endothelial cells, the formation of microaneurysms, basement membrane thickening and blood-retinal barrier breakdown (Cai and Boulton, 2002). In addition to the vascular …”
Section: Introductionmentioning
confidence: 99%
“…The vascular changes that occur in DR are well documented, and include loss of pericytes and endothelial cells, the formation of microaneurysms, basement membrane thickening and blood-retinal barrier breakdown (Cai and Boulton, 2002). In addition to the vascular …”
Section: Introductionmentioning
confidence: 99%
“…All three fundus parameters (NVE, NVD, and FPE) reflect retinal neovascularization, while VEGF and IL-6 are involved in the onset and progression of new vessel formation. 1,2,9 It was suggested that the additional laser was needed to reduce the activity of new vessel formation during surgery in the advanced cases. Therefore, active neovascularization is associated with the progression of PDR.…”
Section: Eyementioning
confidence: 99%
“…1 Activity of PDR and outcome of vitreous surgery may be associated with several factors, but are inconclusive. Numerous cytokines and growth factors have been implicated in the pathogenesis and progression of PDR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations